2018
DOI: 10.1111/dar.12885
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the Thai alcohol policy in regulating alcohol industry's marketing strategies and commercial activities

Abstract: Introduction and Aims. The recognition of the association between the use of alcohol and negative health outcomes have led to the endorsement of the World Health Organization's global strategy to reduce the harmful use of alcohol. Given the capacities, capabilities and sociocultural contexts of Thailand, this study aims to examine the Thai alcohol policy against the global strategy's recommended policy measures for marketing control and identify areas for further policy development. Design and Methods. Semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Opium, heroin, and methamphetamine are being smuggled at the Thai border ( ONCB, 2013 ). Moreover, the volume of alcohol marketing have been problematic for Thai government due to alcohol industry supporting drinking as an integral part of socialisation to provide economic and social benefits ( Kaewpramkusol, Senior, Nanthamongkolchai, & Chenhall, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Opium, heroin, and methamphetamine are being smuggled at the Thai border ( ONCB, 2013 ). Moreover, the volume of alcohol marketing have been problematic for Thai government due to alcohol industry supporting drinking as an integral part of socialisation to provide economic and social benefits ( Kaewpramkusol, Senior, Nanthamongkolchai, & Chenhall, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These included resource constraints, legal loopholes and complications of law, insufficient evidence and lack of monitoring systems to support policy implementation, a low priority among responsible authorities and decision-makers, and limited capacity of implementers and implementing agencies. First, ten out of nineteen studies found resource constraints, such as materials, human resources, and the high workload of police officers, were barriers [ 11 , 17 , 18 , 23 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Second, six studies reported that legal loopholes and legal complications (e.g., requiring precise law interpretation in practice, unclear roles of responsible authorities in legislation) can be a bottleneck for policy implementation [ 11 , 15 , 20 , 26 , 28 , 30 ]. For example, the study in Thailand addressed legal loopholes in alcohol marketing control; advertisement of alcohol products is prohibited, but not non-alcoholic products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations